Cuidadores familiares campesinos : depresión, tiempo de cuidado y dependencia (2014)
Objective: To establish the association of the burden of family caregivers with care time and the degree of functionality of the elderly peasant. Materials and methods: quantitative study with cross-sectional correlational range, with a sample of 50 family caregivers. It was applied: one sociodemographic survey; Zarit scale, measuring caregiver burden, and the Barthel Index, which measures the degree of functional dependence. Results: Family caregivers are usually women (76%); over 60 (50%), married (40%) and single (30%); with low socioeconomic status (94%) and education (66%).No significant association between caregiver burden and the degree of functionality (p = 0.249) was found, nor between caregiver burden and time as caregiver (p = 0.476). Conclusions: A high proportion of rural women are family caregivers. The study reports that caring time and degree of functionality are not predictors of elder care burden on the peasant family caregiver. More research and inquire is needed to determine if there are cultural aspects that influence the experience and meaning construction of care. The need for educational programs for rural carers through processes of self-recognition and self-determination in accordance with their culture and capabilities is suggested.